Extremism Online: Comparative Analysis of the NIS Migrants’ Social Networks - TregubovaNatalya Damirovna; IvanovaAnastasiia Andreevna (Communications. Media. Design, 2020)
The paper addresses the problem of the radicalization of the CIS migrants’ to Russia as it appears on the Internet. The authors formulate two questions for researchers of radicalism and extremism online: To what types of radilization are migrant users most sensitive? How to find extremism and radicalism on the Internet? The paper attempts to answer these questions. The study of potentially extremist sources combines discourse analysis and social network analysis. The empirical base of the study is the corpus of potentially extremist online sources (groups in social media, podcasts, etc.) organized in the framework of a more comprehensive research project. The latter is aimed at comparative analysis of online behavior of migrants to Russia from Azerbaijan, Kazakhstan, Kyrgyzstan, Tajikistan, and Uzbekistan. The paper outlines similarities and differences between radical discourses in which migrants from the CIS countries are involved. The authors pay particular attention to Azerbaijani groups, in which radical discourses are presented in the most extensive and diverse ways. The authors formulate the following research conclusions. First, radical discourses could be divided into nationalism, regional separatism, and religious extremism. Second, the relationships between discourses differ depending on the region. For Azerbaijan, online sources typically combine different discourses, while Central Asian web-sites mainly contain only one type of discourse. Third, the content of the analyzed sources is focused on the problems of the countries of origin or on the global Islamic agenda and has almost no reference to migration to Russia. However, Russia is occasionally mentioned as a country that has a negative impact on the processes in the country of origin. The authors also discuss the limitations of the research and perspectives of studying extremism online.